2021
DOI: 10.3390/app11198870
|View full text |Cite
|
Sign up to set email alerts
|

Air Quality Assessment of a School in an Industrialized Area of Southern Italy

Abstract: In this study, simultaneous monitoring of indoor and outdoor Volatile Organic Compounds (VOCs) was carried out in a school, by both Radiello® cartridges and real-time monitors (Corvus, IonScience Ltd., Fowlmere UK). Moreover, an outdoor air quality assessment was performed with data from an air quality monitoring station (ARPA Puglia) located close to the school. In particular, VOCs, Benzene, Toluene, Ethylbenzene, and Xilenes concentrations, obtained by using Radiello® diffusive samplers, were monitored in tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…Compared to other similar studies conducted in museums [4,15], lower concentration levels of all BTEX were found in this work. The values observed are more in line with the ones observed in other indoor spaces, such as schools [16].…”
Section: E Particulate Mattersupporting
confidence: 88%
“…Compared to other similar studies conducted in museums [4,15], lower concentration levels of all BTEX were found in this work. The values observed are more in line with the ones observed in other indoor spaces, such as schools [16].…”
Section: E Particulate Mattersupporting
confidence: 88%
“…Indeed, benzene concentrations in indoor environments are much higher than those recorded in the outdoor ones, becoming close to the annual average regulatory limit (5 g/m 3 ) of Italian law [34]. It is worth noting that on the base of benzene/toluene (B/T) ratio it is possible to make some hypotheses on possible sources for these pollutants [35]. In outdoor environments this ratio is lower than 1, indicating that sources of BTEX are industrial activities and vehicular traffic.…”
Section: Determination Of Air Concentrationmentioning
confidence: 73%
“…The amount of data regarding their possible effects on cultural heritage, both in the literature and in legislative documents, is lacking. However, volatile organic compounds (VOCs) including BTEX are known to have multiple outdoor and indoor sources [ 22 ] and diagnostic ratios between the different species are useful to establish the most probable sources of pollution [ 21 ]. The preliminary results of this campaign show similar concentrations of benzene and toluene (1.6 and 1.7 µg m −3 , respectively), while measurable amounts of ethylbenzene and xylenes were not observed.…”
Section: Resultsmentioning
confidence: 99%
“…Instead, volatile organic compounds represent an extremely diverse class of compounds, both of primary and secondary origin, with numerous outdoor and indoor sources [ 21 ]. Amongst the VOCs, BTEX (benzene, toluene, ethylbenzene, and xylenes) are the compounds that are usually found in greater concentrations, especially in highly polluted areas [ 22 ]. They typically share common sources, the most important being combustion processes and industrial emissions [ 23 ].…”
Section: Introductionmentioning
confidence: 99%